2008
DOI: 10.1093/ndt/gfn144
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eicosapentaenoic acid on renal function and volume in patients with ADPKD

Abstract: A beneficial effect of EPA on renal function and kidney volume in ADPKD patients could not be confirmed in the present study. Administration of EPA with DHA supplementation and/or longer intervention might be necessary to demonstrate preventive effects of omega3-polyunsaturated fatty acids on progression of ADPKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…Two studies 8,12 were conducted in the United States; 2 10,15, in Japan; 3 9,11,14, in Europe; and 2 13,16, in Australia. Seven studies 8-14 investigated the effect of omega-3 fatty acids on IgA nephropathy, and 2 trials 15,16 evaluated the effect on patients with chronic kidney disease. Study quality was assessed using the Jadad score 18 (Table 1), and a study with a score ≥4 was considered to be of high quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies 8,12 were conducted in the United States; 2 10,15, in Japan; 3 9,11,14, in Europe; and 2 13,16, in Australia. Seven studies 8-14 investigated the effect of omega-3 fatty acids on IgA nephropathy, and 2 trials 15,16 evaluated the effect on patients with chronic kidney disease. Study quality was assessed using the Jadad score 18 (Table 1), and a study with a score ≥4 was considered to be of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Study quality was assessed using the Jadad score 18 (Table 1), and a study with a score ≥4 was considered to be of high quality. Three studies 12,13,16 had a score of 4, while 5 studies 8,9,11,14,15 had a score of 3, and 1 study 10 had a score of 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, DHA supplementation raised safety concerns based on several studies reporting adverse renal effects and reduced survival in diseased animals. The only clinical study of human ARPKD reported no significant effect of dietary n-3 PUFA supplementation on PKD severity [37 ]. With few clinical trials, evidence-based recommendations rely on animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study, ADPKD patients were randomly divided into n = 14 males and n = 6 females (age 47.5 AE 12.5) provided EPA (2.4 g/day ethyl ester) and n = 15 males and n = 6 females (age 46.8 AE 11.4) provided no EPA supplementation for a duration of two years [37 ]. Kidney volume was measured by computed tomography and kidney function was determined using 24-hour urine creatinine clearance.…”
Section: Long-chain N-3 Pufas and Pkdmentioning
confidence: 99%
“…The EPA levels in the RBC membrane in the present model were comparable with those found in patients treated with 2,400 mg EPA for 2 years. 31, 32 Also, in the present study, highly purified EPA was used, which might have been an advantage as compared with the previous studies where fish oil or a combination of EPA and DHA was used. 29 …”
Section: Previous Clinical Studies Of Epa Treatment and Cardiovasculamentioning
confidence: 94%